Root Cause Analysis And Improvement In Windows System Based On Windows Performance Toolkit WPT - Assi, Murtadha J.; Fahad, Assmaa A.; Al-Sarray, Basad (Iraqi Journal of Science, 2022)
Performance issues could be appearing from anywhere in a computer system, finding the root cause of those issues is a troublesome issue due to the complexity of the modern systems and applications. Microsoft builds multiple mechanisms to make their engineers understand what is happening inside All Windows versions including Windows 10 Home and the behavior of any application working on it whether Microsoft services or even third-party applications, one of those mechanisms is the Event Tracing for Windows (ETW) which is the core of logging and tracing in Windows operating system to trace the internal events of the system and its applications. This study goes deep into internal process activities to investigate root cause analysis on Windows 10 Home 20H2, core i5 processor with 4 cores and 8GB of RAM. After simulating workload to get a performance issue, that makes the system and application get unresponsive, then using Windows Performance Toolkit WPT to trace and analyze the event log for root cause investigation. Our results demonstrate analysis works using WPT for decision making such as the reasons of underutilization on CPU and disk, labeling the highlighted patterns, the unbalanced use of system calls in memory, and deciding that the usage preview is the best way to get an idea about applications behavior inside Windows systems resources. Overall improving resources utilization usage and identifying the cause of slowing memory allocation, inefficient disk usage, and throughput.